Mathematical Reflective Thinking of Junior High School Students in Solving Algebra Problems - Desri Rizkia Nurfarihah; Dani Firmansyah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Mathematical reflective thinking is a key higher-order thinking skill in mathematics learning. However, these skills remain underdeveloped for some students, particularly when solving algebraic problems. This study aims to describe seventh-grade students’ mathematical reflective thinking in algebraic problem solving. The participants were all students in Class VIIA at a junior high school in Karawang. Using purposive sampling based on a reflective thinking test, three students were selected to represent high, medium, and low ability categories. Data were collected through a test and follow-up interviews and analyzed qualitatively to capture patterns of reflective thinking across categories. The findings show clear variation among students. High-ability students reflected logically on both the problem-solving process and the correctness of results. Medium-ability students demonstrated partial and inconsistent reflection, often reflecting on steps but not fully evaluating their conclusions. Low-ability students experienced substantial difficulty in monitoring and evaluating their work. These results suggest that students’ reflective thinking develops at different levels in algebraic problem solving, and future research should examine instructional and individual factors that shape these differences.